PENGATURAN DAN PENANGANAN TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DALAM HUKUM PIDANA INDONESIA - Yohana, Katharina; Sudarto (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
The government, local governments, and other state institutions have the obligation and responsibility to provide special protection to child victims of sexual violence. Therefore, it is very interesting and important to further study how the regulation of sexual violence against children in Indonesian criminal law? And how to handle sexual violence against children? To answer these problems, a normative legal research method is used with a statutory and conceptual approach method. Data obtained from primary, secondary, and tertiary legal sources are collected and then analyzed using qualitative data analysis techniques. The results of the study showed that the form of child protection against sexual violence in Indonesia has been regulated in positive legislation. The form of legal protection provided starts from preventing acts of sexual violence against children, protection for child victims of sexual violence and protection for children who are in conflict with the law (child perpetrators) of sexual violence. The form of legal protection for children in Law No. 17 of 2016 is by providing children's rights. The rights of children as victims to the fulfillment of the right to obtain health services and social security according to physical, mental, spiritual, and social needs. On that basis, this handling effort has been mandated by law, not only as a task for the state and government, but more broadly, where the state must provide protection responsibility for children and the entire community regarding the right to obtain health services and social security according to physical, mental, spiritual, and social needs as an effort to restore the condition of children as victims of sexual violence who have long-term trauma.